RETRACTED : HARMONY IN MERARIQ MARRIAGE TRADITION IN LOMBOK AS A MANIFESTATION OF THE QUR’AN - Kusumawardana, M. Ardi (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2021)
This article has been retracted at the request of the Editor-in-Chief. Please see correcting the record https://ejournal.uin-suka.ac.id/ushuluddin/alquran/ethic#correcting Reason: This article contains some duplicate material of a paper that was originally published in Masters thesis, UIN Sunan Kalijaga. https://digilib.uin-suka.ac.id/id/eprint/38665/ One of the conditions of submission of a paper for publication is that authors declare explicitly that all of their work is original and has not appeared in a publication elsewhere. We apologize to readers of the journal that this was not detected during the submission process.